Shuswap Community Handbook - Jack, Rita (Author); Matthew, Marie (Author); Matthew, Robert (Author); Secwepemc Cultural Education Society (Author); Aboriginal Education Branch, Ministry of Education (Funder); Ministry Responsible for Multi-Culturalism and Human Rights, Province of British Columbia (Funder) (Secwepemc Cultural Education Society, 1993)
The "Teachers Cross Cultural Awareness Handbook", was developed to present information on the culture, history, and contemporary lifestyle of Secwepemc people. It is intended that this manual will serve as background information and as a resource for teachers of Shuswap First Nations children. It is anticipated that providing teachers with background knowledge and methods for communicating with communities will lead to further cooperation between the Provincial education system and the Shuswap communities for the success of First Nations students. Not peer reviewed Historic booklet